2010
DOI: 10.1016/j.neulet.2010.02.067
|View full text |Cite
|
Sign up to set email alerts
|

Changes in purines concentration in the cerebrospinal fluid of patients experiencing pain: A case-control study

Abstract: This study analyzes the relationship between extracellular purines and pain perception in humans. Cerebrospinal fluid (CSF) levels of purines and their metabolites were compared between patients displaying acute and/or chronic pain syndromes and control subjects. The CSF levels of IMP, inosine, guanosine and uric acid were significantly increased in the chronic pain group and correlated with pain severity (P<0.05). Patients displaying both chronic and acute pain presented similar changes in the CSF purines con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…Cut-off and reference ranges were in agreement with those indicated in the literature. Discrepancies in the concentrations of adenosine, inosine and xanthine occurred between our values and those reported by HPLC-UV by Schmidt et al 18 For all three compounds, higher values were reported in our work and in other work, [19][20][21][22][23][24][25] even though no interference or co-elution have been observed in our work. To the best of our knowledge, the present study is the first to report CSF reference concentrations for 2,8-dihydroxyadenine, 5-hydroxymethyluracil, orotic acid, orotidine, pseudouridine, 2-deoxyguanosine, AICAriboside and SAICAR.…”
Section: Purines and Pyrimidines Analysiscontrasting
confidence: 95%
“…Cut-off and reference ranges were in agreement with those indicated in the literature. Discrepancies in the concentrations of adenosine, inosine and xanthine occurred between our values and those reported by HPLC-UV by Schmidt et al 18 For all three compounds, higher values were reported in our work and in other work, [19][20][21][22][23][24][25] even though no interference or co-elution have been observed in our work. To the best of our knowledge, the present study is the first to report CSF reference concentrations for 2,8-dihydroxyadenine, 5-hydroxymethyluracil, orotic acid, orotidine, pseudouridine, 2-deoxyguanosine, AICAriboside and SAICAR.…”
Section: Purines and Pyrimidines Analysiscontrasting
confidence: 95%
“…In vivo human studies have shown higher levels of guanosine in patients suffering from chronic pain and it is correlated with pain severity [ 174 ]. In pregnant women levels of GTP and guanosine are increased in CSF compared to non-pregnant women and acute pain labor is negatively correlated with adenosine levels [ 175 ].…”
Section: Implications Of Guanosine Effects Towards a Clinical Strategmentioning
confidence: 99%
“…The authors suggest that shifts in neuronal and glial energy metabolism might be correlated with pain transmission mechanisms. CSF levels of inosine and other purines associated with ATP metabolism are significantly increased in chronic pain patients compared to control patients and are significantly correlated with pain intensity measured using a visual analog scale ( Schmidt et al, 2010 ). Conversely, serum purine metabolites are increased in fibromyalgia patients (i.e., the dysregulation of pain pathways leading to central sensitization) compared to controls.…”
Section: Inosine and Painmentioning
confidence: 99%